DUKUNGAN MANAJEMEN PUNCAK MEMODERASI PENGARUH KAPASITAS STAFF TERHADAP KINERJA ORGANISASI - Dwika Lodia Putri; Farwitawati, Reni; Masirun (Jurnal Daya Saing, 2025)
This study examines the effect of staff capacity on the performance of higher education institutions (HEIs) in Riau, with a focus on the moderating role of top management support. In the context of higher education, staff capacity, which includes adequate knowledge, skills, and experience, is expected to improve operational effectiveness, especially in the areas of teaching, research, and services. However, the effect of staff capacity cannot always be realized without adequate support from top management. Therefore, this study uses Resource Dependency Theory (RDT) to examine the role of top management support in moderating the relationship between staff capacity and HEI performance. This study collected data from 382 lecturers at universities in Riau using simple random sampling technique. The results showed that staff capacity has a significant positive influence on HEI performance, with top management support serving as a moderator that strengthens the relationship. The findings indicate the importance of synergy between staff capacity and top management support in improving university performance. This study contributes to the education management literature by providing empirical evidence on the influence of staff capacity and top management support on organizational performance in the higher education sector